Intra-repetition variable resistance training: part 1-an overview - Ignacio J. Chirosa; S. Baena; Miguel Ángel Soria; Iker Javier Bautista; Luís Javier Chirosa (Asociación Española de Ciencias del Deporte, 2014)
This series of reviews focuses on changes in external resistance during a repetition, and the ability to generate maximal muscular strength and power in a repetition. Part 1 focuses on the types and effects of Variable Resistance on neuromuscular adaptations. Part 2, which will follow in an upcoming edition of EJHM, explores the practical applications and methodological findings to the design of training programs that most effectively enhance maximal force production. The use of new strategies will help athletes and specialists improve performance, and will increase effectiveness of strength-training programs. The ability to generate maximal force is influenced by the time available to develop force, the magnitude of the external resistance, and the amount of resistance progressively added or reduced. This Part analyzes the most common ways of modifying external resistance using chains and elastic bands. These reviews discuss acute changes in the muscle environment and the impact that this has in maximal force production over different expressions of strength. Intra-Repetition Variable Resistance (irVR) training has been shown to impact different neuromuscular factors in many specific ways. Therefore, an understanding of the biological basis of maximal force production is essential for developing training programs that effectively enhance human strength capacity.